How do you express sin theta - cottheta + tan^2 theta in terms of cos theta ? Trigonometry Trigonometric Identities and Equations Fundamental Identities 1 Answer Ratnaker Mehta Jun 10, 2016 sqrt(1-cos^2theta -- costheta/sqrt(1-cos^2theta+(1 -cos^2theta)/cos^2theta Explanation: sintheta= sqrt(1-cos^2theta cottheta=costheta/sintheta=costheta/sqrt(1-cos^2theta tan^2theta= sec^2theta - 1=1/(cos^2theta) - 1 = {1-cos^2theta}/cos^2theta Hence, the reqd. expression =sqrt(1-cos^2theta -- costheta/sqrt(1-cos^2theta+(1 -cos^2theta)/cos^2theta Answer link Related questions How do you use the fundamental trigonometric identities to determine the simplified form of the... How do you apply the fundamental identities to values of theta and show that they are true? How do you use the fundamental identities to prove other identities? What are even and odd functions? Is sine, cosine, tangent functions odd or even? How do you simplify sec xcos (frac{\pi}{2} - x )? If csc z = \frac{17}{8} and cos z= - \frac{15}{17}, then how do you find cot z? How do you simplify \frac{\sin^4 \theta - \cos^4 \theta}{\sin^2 \theta - \cos^2 \theta} using... How do you prove that tangent is an odd function? How do you prove that sec(pi/3)tan(pi/3)=2sqrt(3)? See all questions in Fundamental Identities Impact of this question 1390 views around the world You can reuse this answer Creative Commons License